Telitacicept as double-targeted therapy for myasthenia gravis coexisting with connective tissue disease: three case reports - Yang, Yingying; Zhu, Ying; Zhu, Ruixia (Frontiers in Immunology, 2025)
Myasthenia gravis (MG) and connective tissue diseases (CTD) are both B-cell-mediated, antibody-associated autoimmune diseases that share similar mechanisms of immune dysfunction. The coexistence of MG and CTD is a rare phenomenon, and its management remains challenging. Here, we report three cases of coexisting MG and CTD—specifically systemic lupus erythematosus and Sjögren’s syndrome, and all three patients presented significant improvement 4 weeks after initiation of treatment with telitacicept. Minimal symptom expression (MSE) was achieved after 4, 6, and 7 weeks of treatment with telitacicept, for patients one-to-three, respectively. This therapy also enabled a reduction in prednisone dosage, with clinical symptoms of CTD remaining well controlled. These findings present preliminary evidence supporting Telitacicept as an effective treatment and a double-target therapy for the management of MG-CTD.